Note: Optimal Ordering Decisions with Uncertain Cost and Demand Forecast Updating - Gurnani, Haresh; Tang, Christopher S. (Management Science, 1999)
We determine the optimal ordering policy for a retailer who has two instants to order a seasonal product from a manufacturer prior to a single selling season. While the demand is uncertain, the retailer can improve the forecast by utilizing the market signals observed between the first and second instants. However, because of the nature of the manufacturing environment, the unit cost at the second instant is uncertain and could be higher (or lower) than the unit cost at the first instant. To determine the profit-maximizing ordering strategies at both instants, the retailer has to evaluate the trade-off between a more accurate forecast and a potentially higher unit cost at the second instant. We present a nested newsvendor model for determining the optimal order quantity at each instant and characterize the conditions under which it is optimal for the retailer to delay its order until the second instant.